Feedstock characterisation of titanium alloy mix with palm stearin binder system for metal injection moulding - Mohamad Nor, Nor Hafiez; M., Norhamidi; Ahmad, Sufizar; Ibrahim, Mohd. Halim I.; Murtadhahadi, Murtadhahadi; Jamaludin, Khairur Rijal (2009)
This paper presents the characterization of MIM feedstock consisting 90wt% of titanium alloy (Ti-6Al-4V) powder mix with binder 60wt% palm stearin and 40wt% polyethylene. The characterization of Ti-6Al-4V alloy powder, binders and feedstock includes scanning electron micrograph (SEM), thermogravimetric analysis (TGA), differential scanning calorimeter (DCS) and rheological test were established. Rheological results exhibited pseudoplastic or shear thinning flow behaviour, where its viscosity decreased with increasing shear rate. The feedstock viscosity also decreased with increasing temperature and was found to be suitable for moulding